1st annual Colorado rare plant symposium: meeting minutes - Colorado Natural Heritage Program, author (Colorado State University. Libraries, 2004)
Includes minutes from the first Annual Colorado Rare Plant Symposium. The purpose of the symposium was to foster knowledge exchange and networking, and to provide updates to distribution, abundance, and threats of all federally listed Threatened, Endangered, or Candidate plants occurring in Colorado.
Minutes from the first annual Colorado rare plant symposium
Symposium held on September 17, 2004 at the Olympian Hall in Steamboat Springs, Colorado.
Keywords: Rare plants -- Colorado -- Identification; Endemic plants -- Colorado -- Identification; Endangered plants -- Colorado -- Identification